Function and Meaning of Madurese Folk Songs and Literary Expressions in Sumenep Regency - Maulid Taembo; Wevi Lutfitasari; Nur Afifah; Ayu Arifin (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2024)
Oral literature, such as folk songs and literary expressions (poems and proverbs), contains the local wisdom of the community that owns it. This research aims at explaining the function and meaning contained in Madurese folk songs and literary expressions. The description of the meaning and function of Madurese literature provides many valuable lessons regarding Madurese local wisdom. It is one of ways to maintain and develop the local culture. Research data was collected through documentation, observation and interview methods using note-taking and recording techniques. This research used qualitative descriptive analysis in semiotic study. Based on research results, Madurese folk songs and literary expressions have many functions such as giving advice, increasing joy, informing certain event procedures, showing certain beliefs, and increasing self-confidence and enthusiasm for working. Besides, Madurese folk songs and literary expressions have valuable meanings, such as religious, struggle, perseverance, patience, discipline, self-respect, beauty, manners of way, togetherness, hard work, sincerity, and honesty. These functionsare still maintained today. In fact, the meaning contained in these folk songs and literary expressions always accompanies the behavior and activities of the Madurese people. In brief, folk songs and literary expressions in Sumenep have various functions and dense meanings in daily activities. Keywords: function, meaning, folksongs, expressions, Madura local wisdom